Comparative Analysis of Project Completion Forecasting Using Earned Value Management, Earned Schedule, and Program Evaluation and Review Technique - Kevin Ardian Krisanto; Mega Waty (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
This study evaluates schedule performance and forecasts the completion time of a restaurant construction project in the PIK 2 area by integrating Earned Value Management (EVM), Earned Schedule (ES), and the Program Evaluation and Review Technique (PERT). Unlike previous studies that apply these methods separately or through pairwise comparisons, this study integrates deterministic performance evaluation and probabilistic schedule forecasting to provide a comprehensive framework for project control. The project was evaluated at week 13 of a planned 37-week duration. EVM produced a Schedule Variance (SV) of ?Rp1,051,310,568 and a Schedule Performance Index (SPI) of 0.774, forecasting completion at week 48. ES generated a Time Variance (SV(t)) of ?4.44 weeks and an SPI(t) of 0.659, projecting completion at week 56. PERT estimated an expected project duration of 122.67 days and forecast completion at week 42 without acceleration and week 40 with acceleration at a 95% confidence level. The findings demonstrate that integrating EVM, ES, and PERT provides complementary insights for monitoring project performance, quantifying schedule uncertainty, and improving completion forecasting.